2018
DOI: 10.1177/1084822318803861
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Among Japanese Home-Visit Care Workers

Abstract: The present qualitative study aims to shed light on the job satisfaction of home-visit care workers in Japan. A total of 19 participants were recruited from two rural, three suburban, and one urban area in and around Nagoya city. The qualitative data were collected through individual or group interviews from May to August of 2017. The interviews were conducted using an open-ended questionnaire concerning job satisfaction. Qualitative content analysis was used to systematically identify ideas and patterns emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
9
1
1
Order By: Relevance
“…The study findings are quite similar to other studies conducted in Japan. A previous study conducted on job satisfaction among Japanese home visit care workers depicted that they enjoy working in a congruent environment with highly valued communication 13 . Another study conducted among nursing home staff providing terminal care revealed providing elderly care acts as a motivational factor 15 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The study findings are quite similar to other studies conducted in Japan. A previous study conducted on job satisfaction among Japanese home visit care workers depicted that they enjoy working in a congruent environment with highly valued communication 13 . Another study conducted among nursing home staff providing terminal care revealed providing elderly care acts as a motivational factor 15 .…”
Section: Discussionmentioning
confidence: 97%
“…A previous study conducted on job satisfaction among Japanese home visit care workers depicted that they enjoy working in a congruent environment with highly valued communication. 13 Another study conducted among nursing home staff providing terminal care revealed providing elderly care acts as a motivational factor. 15 In contrast, a study conducted in Sapporo demonstrated high dissatisfaction regarding wages and professional relationships among home careworkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric oncology social workers help families manage day-to-day challenges associated with a cancer diagnosis and its treatment 12,13 . The social worker sees the family members and evaluates with them physician statements 14,15 .…”
Section: Introductionmentioning
confidence: 99%